The Arctic Playground of Europe: Sir Martin Conway’s Svalbard - Ryall, Anka (Nordlit, 2015)
The development of tourism is a significant aspect of the processes of modernity in the High Arctic. This article discusses the British art historian and mountaineer Sir William Martin Conway’s two travelogues, The First Crossing of Spitsbergen (1897) and With Ski and Sledge over Arctic Glaciers (1898), in terms of a pioneering tourist approach to the archipelago of Svalbard. Unlike earlier yachting tourists, Conway described a journey into the uncharted interior of the main island, Spitsbergen. His books are therefore narrated as exploration accounts and following many of the demands of that genre, such as an emphasis on mapping, natural science and being the first. However, they may also be read as guidebooks for other discerning and undaunted British gentleman travellers. Inspired by the art critic John Ruskin’s “science of aspects”, which combined accurate scientific observations and practical knowledge with an imaginative and aesthetic response to the landscape, Conway attempts to give his readers a positive sense of the qualities of the Arctic. At the same time, he promotes Svalbard as an Arctic “Playground of Europe”, where adventurous Alpinists in addition to climbing unknown mountains and glaciers could find fraternal domesticity far away from home around the hearth of the campfire. In this way Conway locates natural beauty, life and recreational opportunities where travellers before him had only described desolation and death.